Patients’ Satisfaction with Obstetrics-Gynecology, and Pediatric Healthcare Services in Vietnam: A Multicentre Cross-Sectional Study - Minh Hoang P; Giang LT; Tran MD (Dove Medical Press, 2023)
Phuong Minh Hoang,1,2 Long Thanh Giang,2 Minh Dien Tran3 1Department of Finance and Accounting, National Children's Hospital, Hanoi, Vietnam; 2Faculty of Economics, National Economics University, Hanoi, Vietnam; 3National Children's Hospital, Hanoi, VietnamCorrespondence: Phuong Minh Hoang, Department of Finance and Accounting, National Children's Hospital, 18/879 La Thanh, Lang Thuong Ward, Dong Da District, Hanoi, 100000, Vietnam, Tel +84982425452, Email hoangphuong.39.2018@gmail.comPurpose: Despite improvements in maternal and child health in Vietnam, sustained efforts are required to improve healthcare quality and resolve persistent disparities, highlighting the universal significance of customer satisfaction in healthcare. This study aims to assess patient satisfaction with healthcare services and associated factors at obstetrics-gynecology and pediatric hospitals across different geographical areas in Vietnam.Patients and Methods: A cross-sectional study was conducted in 2019 among 647 patients or caregivers of hospitalized children at three major obstetrics-gynecology and pediatric hospitals, representing different geographical areas in Northern Vietnam. A Ministry of Health-approved satisfaction instrument was utilized to assess patient satisfaction. The instrument included 31 items measuring five dimensions of perceived satisfaction. Exploratory factor analysis examined the construct validity of the satisfaction measurement, and multivariate linear regression determined the factors associated with patient satisfaction.Results: Among the 643 participants, 520 were female (89.87%), and nearly half were aged 18- 29 years old (43.7%). Factor analysis revealed three dimensions: "Competency and Outcomes", "Accessibility and Procedures", and "Facilities and Equipment", with mean domain scores of 4.6 ± 0.43, 4.28 ± 0.67, and 4.53 ± 0.51, respectively. The proportion of participants completely satisfied with overall service quality was 48.52%, and expectation met was 34.53%. Multivariate linear regression indicated that patients from hospitals in the Red River Delta region had higher satisfaction scores than those in the Middle region across all domains (p< 0.05). Higher health insurance coverage was associated with increased satisfaction, while education level, economic status, and ethnicity also influenced satisfaction.Conclusion: The study revealed moderate to high levels of satisfaction among patients at three major obstetrics-gynecology and pediatric hospitals in northern Vietnam. The findings may provide useful evidence for implementing hospital quality control in Vietnam, focusing on patient-centered goals.Keywords: patient preference, quality of care, developing countries